H2 emission in the low-ionization structures of the planetary nebulae NGC 7009 and NGC 6543. Issue 3 (21st February 2020) - Akras, Stavros; Gonçalves, Denise R; Ramos-Larios, Gerardo; Aleman, Isabel
ABSTRACT: Despite the many studies in the last decades, the low-ionization structures (LISs) of planetary nebulae (PNe) still hold several mysteries. Recent imaging surveys have demonstrated that LISs are composed of molecular gas. Here, we report H2 emission in the LISs of NGC 7009 and NGC 6543 by means of very deep narrow-band H2 images taken with NIRI@Gemini. The surface brightness of the H2 1-0 S(1) line is estimated to be (0.46–2.9)× 10 −4 erg s −1  cm −2  sr −1 in NGC 7009 and (0.29–0.48)× 10 −4 erg s −1  cm −2  sr −1 in NGC 6543, with signal-to-noise ratios of 10–42 and 3–4, respectively. These findings provide further confirmation of hidden H2 gas in LISs. The emission is discussed in terms of the recent proposed diagnostic diagram R (H2 ) = H2  1-0 S(1)/H2  2-1 S(1) versus R (Brγ) = H2  1-0 S(1)/Brγ, which was suggested to trace the mechanism responsible for the H2 excitation. Comparing our observations to shock and ultraviolet (UV) molecular excitation models, as well as a number of observations compiled from the literature showed that we cannot conclude for either UV or shocks as the mechanism behind the molecular emission.